Issues of peasant colonization of the Steppe Region in the State Duma of the Russian Empire (1906-1917) - Alimbay Нұрсан; Kabyldinov З.; Smagulov Б. (Turkic Studies Journal, 2023)
The article considers the process of participation of Kazakh deputies of the State Duma (hereinafter – the Duma) of the Russian Empire of the first and second convocations in the discussion and practical solution of the peasant colonization of the Kazakh region, which was aggressive in nature. The novelty of this part of the study is based on the involvement of factual data that had not previously entered scientific circulation, especially official documents of the Duma, it was possible to find out the reasons for the «inferior» participation of Kazakh deputies in the legislative activities of the Duma of the first two convocations. The reason was the discriminatory attitude towards representatives of the Kazakh population on the part of the tsarist authorities. They artificially delayed the official registration of elected Kazakhs as members of the Duma. In relation to an outstanding leader of the Kazakh political forces, Alikhan Bukeikhan, a deliberately fictitious criminal case was opened. The activities of those members of the III and IV Duma who represented various political forces and parties in the empire were also studied in detail. Special attention is paid to the study of political platforms and positions of individual deputies regarding the process of forced settlement of peasants in communal tribal territories of Kazakh pastoralists. The deprivation by the imperial authorities of the so-called «foreigners», including Kazakhs, the right to be elected and to elect, which followed immediately after the dissolution of the II Duma, quite eloquently demonstrates the true colonization policy of the Russian Empire, including in the field of land relations and land management.